2014
DOI: 10.1155/2014/461841
|View full text |Cite
|
Sign up to set email alerts
|

Deliberate Self-Poisoning Presenting to an Emergency Medicine Network in South-East Melbourne: A Descriptive Study

Abstract: Background. Deliberate self-poisoning (DSP) comprises a small but significant proportion of presentations to the emergency department (ED). However, the prevalence and patient characteristics of self-poisoning attendances to EDs in Victoria have not been recently characterised. Aim. To identify and compare the characteristics of adult patients presenting to the three EDs of Monash Health following DSP. Methods. Retrospective clinical audit of adult DSP attendances between 1st July 2009 and 30th June 2012. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
20
3
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 20 publications
5
20
3
2
Order By: Relevance
“…However, studies from the other nations like Iran, Tanzania, Australia and United Kingdom revealed contrary results to our study, as medicines (sedatives, analgesics and antidepressants) were the most implicated agents in deliberate poisoning. However, in Ethiopia, Brazil, Caribbean and Ecuador, the results were similar to ours showing that pesticides were the most implicated agents in poisoning .…”
Section: Discussionsupporting
confidence: 90%
“…However, studies from the other nations like Iran, Tanzania, Australia and United Kingdom revealed contrary results to our study, as medicines (sedatives, analgesics and antidepressants) were the most implicated agents in deliberate poisoning. However, in Ethiopia, Brazil, Caribbean and Ecuador, the results were similar to ours showing that pesticides were the most implicated agents in poisoning .…”
Section: Discussionsupporting
confidence: 90%
“…The most often used substances was benzodiazepines (36,6%), which is similar to previous studies ranging from 39%-61% [18,39] and the second most frequent substance was analgesic. This pattern was different from a study in the UK where the analgesic was responsible for the most selfpoisoning cases [9], a study in the USA where poisoning by unspecified drugs or medicinal substances accounted for the highest number of self-poisoning [10] and a studies from Korea where the ingestion of pesticides is the principal agent of selfpoison among patients over the age of 50 Year [17].…”
Section: Discussionsupporting
confidence: 89%
“…The present study describes the characteristics of adolescents presenting to an Australian ED network with DSP. A previous study of adults, conducted in the same healthcare network, revealed that 0.7% of adult ED presentations were the result DSP . In comparison, we found that 2% of adolescent presentations to the same ED network were related to DSP.…”
Section: Discussioncontrasting
confidence: 59%
“…This is consistent with previous studies of adolescent self‐poisoning. However, it differs from studies of adult overdose where benzodiazepines, as a group, are the most common substances ingested . This difference suggests that adolescents might have less access to prescription medications.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation